A variable turbulent Prandtl number model for simulating supercritical pressure CO2 heat transfer. (November 2016) - Tang, Guoli; Shi, Hang; Wu, Yuxin; Lu, Junfu; Li, Zhouhang; Liu, Qing; Zhang, Hai
Highlights: The effects of Pr t on heat transfer calculation were analyzed. A new variable Pr t model (TWL model) was proposed. TWL model improves the accuracy of prediction on heat transfer deterioration. The maximum Pr t appears in the buffer layer when HTD occurs. Abstract: In order to predict heat transfer deterioration (HTD) of supercritical pressure fluid correctly and to investigate the HTD mechanism, the effect of turbulent Prandtl number ( Pr t ) on numerical simulation was theoretically analyzed. Based on such analysis, a new turbulent Pr t model (TWL model) was proposed. Numerical simulations of the supercritical pressure CO2 heat transfer in vertical heated tubes were conducted with the proposed Pr t model as well as two other previous Pr t models and two constant Pr t numbers. The performance of the new Pr t model was validated by comparing with 14 reported heat-transfer experimental data, especially for the HTD cases. The comparison showed that a better prediction of wall temperature can be achieved with the proposed Pr t model in most of the validations, especially for the HTD cases. When HTD occurs, turbulent mixing was restrained in the buffer layer since an "M" shape of velocity profile is formed under the buoyancy effect. The maximum predicted Pr t value with TWL model also appears in the buffer layer, while the maximum predicted Pr t value with other models appear in the viscous sub-layer. Such Pr t profile restrains the turbulent mixing contribution to heat transfer further. Although the turbulent mixing contribution is still several times higher than molecular conduction contribution in the buffer layer when HTD occurs, it's not strong enough to diffuse energy from near wall region to the bulk region.